2012
DOI: 10.3201/eid1809.111296
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Influenza Viruses in Poultry and Swine, West Africa, 2006–2008

Abstract: West Africa might be an animal influenza–free zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
7
40
0
2
Order By: Relevance
“…These results may also suggest persistent circulation of virulent NDV strains in local chickens independent of a recognized epizootic. In a recent sur- veillance study focused on avian influenza, we have shown that 32% of bird serum samples from Togo were positive for NDV antibodies by the HI test (28). The high seroprevalence of NDVs may indeed explain in part the absence of clinical signs, despite their virulent pathotype.…”
Section: Discussionmentioning
confidence: 99%
“…These results may also suggest persistent circulation of virulent NDV strains in local chickens independent of a recognized epizootic. In a recent sur- veillance study focused on avian influenza, we have shown that 32% of bird serum samples from Togo were positive for NDV antibodies by the HI test (28). The high seroprevalence of NDVs may indeed explain in part the absence of clinical signs, despite their virulent pathotype.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out a large-scale active surveillance study of animal influenza in Togo from 2009 through 2014 with close to 10 000 avian and swine swabs tested for the presence of influenza virus genome. As observed in the neighboring Benin and Côte d’Ivoire, none of the animal swabs collected in Togo through 2012 had been positive for influenza A virus, nor had any animal serum tested positive for influenza A virus antibodies (Couacy-Hymann et al, 2012). Again from 2011 through 2014, no avian samples tested positive for influenza virus genome or antibody in the 3 countries (Fuller et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Since influenza virus is excreted continuously in faeces for only about 12 days in birds (Henaux and Samuel, 2011;Couacy-Hymann et al, 2012), it is possible that the period of virus shedding could have been missed in the birds sampled. It could also be due to too low titres of the virus in faeces which makes it undetectable by RT-PCR.…”
Section: Discussionmentioning
confidence: 99%